Does ecosystem sensitivity to precipitation at the site‐level conform to regional‐scale predictions?. Issue 3 (March 2016) - Wilcox, Kevin R.; Blair, John M.; Smith, Melinda D.; Knapp, Alan K.
Abstract: Central to understanding global C cycle dynamics is the functional relationship between precipitation and net primary production (NPP). At large spatial (regional) scales, the responsiveness of aboveground NPP (ANPP) to interannual variation in annual precipitation (AP; ANPPsens ) is inversely related to site‐level ANPP, coinciding with turnover of plant communities along precipitation gradients. Within ecosystems experiencing chronic alterations in water availability, plant community change will also occur with unknown consequences for ANPPsens . To examine the role plant community shifts may play in determining alterations in site‐level ANPPsens, we experimentally increased precipitation by 35% for two decades in a native Central U.S. grassland. Consistent with regional models, ANPPsens decreased initially as water availability and ANPP increased. However, ANPPsens shifted back to ambient levels when mesic species increased in abundance in the plant community. Similarly, in grassland sites with distinct mesic and xeric plant communities and corresponding 50% differences in ANPP, ANPPsens did not differ over almost three decades. We conclude that responses in ANPPsens to chronic alterations in water availability within an ecosystem may not conform to regional AP–ANPP patterns, despite expected changes in ANPP and plant communities. The result is unanticipated functional resistance to climate change at the site scale.